IMPLEMENTASI DAN UPAYA PENEGAKAN HUKUM TINDAK PIDANA PENCUCIAN UANG DALAM TRANSAKSI PERBANKAN DI INDONESIA - Nur Mustakim; Rukmana Amanwinata (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2020)
Money laundering is a criminal offense to attempt to launder money earned from the proceeds of crime in order to be a legitimate money through the banking sector. The criminal act is done through the medium of banks, of course, this leads to a negative effect on the banking system, but in law enforcement is not an objective consideration of the balance between the interests of the accused and the interests of society.